Аналіз структури аптечних закладів, що перебувають у спільній власності територіальних громад, крізь призму фармацевтичної безпеки держави - Панькевич, О.; Ткаченко, Наталя Олександрівна; Шунькіна, С.; Громовик, Б.; Pankevych, O.; Tkachenko, N. O.; Shunkina, S.; Hromovyk, B. (Інститут мікробіології та імунології ім. І. І. Мечникова НАМН України, 2023)
Introduction: The priority component of the state policy in the field of health care is the development of pharmaceutical safety, for which there are typical threats, related to import dependence, pseudo-elasticity in the development of the retail pharmaceutical market, the imbalance of the system of special medical supply, the total depreciation of pharmaceutical education and the occupation, as well as the significant reduction of research of branch and university pharmaceutical science in Ukraine. The purpose of the work was to conduct an analysis of the structure of pharmacy establishments in the common property of territorial communities through the prism of pharmaceutical safety of the state. Material & methods. The following methods were used in the research: legal analysis, content analysis, system approach, observation, comparison and generalization, abstraction. The materials for the research were: the normative and legal framework related to the pharmaceutical industry, informational messages of the central executive authorities, scientific publications of domestic scientists, and data from 42 responses to the requests for public information (inquiries) that were sent to 22 regional councils (RC) and Kyiv City State Administration (KCSA). Results & discussion. After summarizing the data of responses to requests sent to 22 RC and KCSA, we have established the presence of 565 pharmacy establishments (PE) that are in the common property of territorial communities, 14 of which were pharmacy warehouses (bases), 370 pharmacies and 181 pharmacy points. The extremely uneven distribution of PE of communal form of ownership in regions of Ukraine has been found. At the same time, in three regions - Kyiv, Cherkasy, and Mykolaiv, which is 13.63% of the general analyzed quantity, almost half (48.85%) of PE in the common property of territorial communities is located. On the other hand, in Kyiv, Odesa, Rivne, and Sumy regions (18.18% of regions) there are no such types of PE. It was found that PE of Kyiv and Volyn regions, which are in the common property of territorial communities, were exempted from paying rent under property lease agreements during the hostilities, and Ivano-Frankivsk and Zakarpattia regions have reduced rent by 30 and 50%, respectively. In turn, for PE of Kirovohrad region, the amount of rent was set at the level of 2 UAH per square meter, and for Lviv region - 1% of the value of real estate, determined by conducting of an independent assessment. Taking into account the abovementioned, it can be stated that 322 or 55.0% of PE, which are in the common property of territorial communities of Ukraine, have preferences in rent. Conclusion. Threats to the pharmaceutical security of the state were summarized, and the need for regulatory and legal settlement of the issue of creating stocks of medicines and medical supplies in case of martial law was confirmed. An uneven distribution of PE, which are in the common property of territorial communities of Ukraine, has been established, which does not make it possible to adequately provide the population with medicines and medical supplies or to form such a reserve both in peacetime and in conditions of martial law. The non-uniformity of lease preferences of PE, which are in the common property of territorial communities of Ukraine, was clarified
Analysis of the structure of pharmacy establishments, that are in the common property of territorial communities, through the prism of pharmaceutical safety of the state
Keywords: structure of pharmacy establishments; analysis; territorial communities; pharmaceutical safety of the state